2020
DOI: 10.1177/0885066620934392
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Variation in Carotid Artery Peak Systolic Velocity Is Unable to Predict Fluid Responsiveness in Spontaneously Breathing Critically Ill Patients When Assessed by Novice Physician Sonologists

Abstract: Background: Respiratory variation in carotid artery peak systolic velocity (ΔVpeak) assessed by point-of-care ultrasound (POCUS) has been proposed as a noninvasive means to predict fluid responsiveness. We aimed to evaluate the ability of carotid ΔVpeak as assessed by novice physician sonologists to predict fluid responsiveness. Methods: This study was conducted in 2 intensive care units. Spontaneously breathing, nonintubated patients with signs of volume depletion were included. Patients with atrial fibrillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A study by Abbasi et al [ 23 ] showed that novice sonologists are unable to determine fluid responsiveness based on changes in FTc or carotid blood flow. Another study [ 24 ] showed that ΔVpeak could not accurately predict fluid responsiveness when evaluated by novice sonologists. These studies suggest that some level of expertise may be required to correctly evaluate carotid ultrasound-derived FTc and ΔVpeak to determine fluid responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Abbasi et al [ 23 ] showed that novice sonologists are unable to determine fluid responsiveness based on changes in FTc or carotid blood flow. Another study [ 24 ] showed that ΔVpeak could not accurately predict fluid responsiveness when evaluated by novice sonologists. These studies suggest that some level of expertise may be required to correctly evaluate carotid ultrasound-derived FTc and ΔVpeak to determine fluid responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…There were multiple reasons for hemodynamic instability. The majority were unspecified/heterogeneous [ 9 , 25 , 29 , 32 , 34 , 35 , 37 , 39 ] or septic shock [ 26 , 30 , 31 , 33 , 36 , 40 ], with a minority of studies having cohorts of patients with haemorrhagic shock [ 27 ] or cardiogenic shock [ 38 ]. A fluid challenge was administered either by crystalloid bolus [ 27 31 , 34 , 37 , 40 ], passive leg raise (PLR) [ 25 , 26 , 32 , 38 , 39 ], or a combination of the two [ 9 , 33 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Crystalloid volume was determined by weight (6-7 ml/kg) or a predetermined value (200 ml–500 ml). The reference standards most commonly used were left ventricular outflow tract (LVOT) velocity time integral (VTI) [ 26 , 27 , 31 , 33 , 34 , 37 , 38 ] and noninvasive cardiac output monitor (NICOM) (Cheetah Medical, Inc) [ 9 , 25 , 28 , 29 ], with some studies used pulmonary artery catheter (PAC) [ 32 , 36 , 40 ], pulse contour cardiac output (PiCCO) (PULSION Medical Systems AG, Munich, Germany) [ 30 , 35 ], and FloTrac (Edwards Lifesciences, Irvine, CA, USA) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, one group found that carotid artery peak velocity variation worked well in spontaneously breathing preoperative neurosurgery patients, 51 and another group could not replicate this finding in critically ill patients. 54 Conflicting Data and Sources of Error Yet, not all investigations have confirmed the common carotid artery as a successful site to infer SV change. Girotto et al found that carotid blood flow was sensitive but not specific for detecting significant change in cardiac index (CI), 55 and Abbasi et al found that novice sonographers were unable to use either carotid blood flow or FTc as adequate CI surrogates.…”
mentioning
confidence: 99%